E-RRANDS: AN ANDROID-BASED APPLICATION FOR SHOP AND SHIP OF CONCIERGE SERVICES INTEGRATING GEOLOCATION TECHNOLOGY - Tuano, Melissa T; Martinez, Dylan L; Cayabyab, Ana Liza F; Sapin, SHERW B; Lanuang, Manuel C (Journal of Agriculture and Technology Management, 2021)
Economic shutdown in the Philippines caused by COVID19 pandemic leaves an additional five million (5.35%) jobless Filipinos with an overall 17.7 percent unemployment rate as of May 2020. Despite the continuous decrease of global commerce, e-commerce is one of the industries alongside the health industry, which shows opposite results amidst pandemic. However, to adapt to the new post COVID world, micro, small and medium enterprises (the MSME sector) or the surviving entrepreneurs need (advised) to include delivery service operation systems in their businesses. Those who were unable to adapt, especially the non-essential business, resorted to closing permanently or at risk of closing. E- rrands is an android application that can help bridge the gap between customers and businesses by providing a third-service provider through the application. This study adopted the Agile Scrum Methodology phases as the approach in the development of E-rrands. The study utilized the developmental-quantitative research design involving two sets of respondents, the end users and the IT experts. The overall rating of the developed E-rrands android application based on ISO 25010 got a 3.73 mean score and a strongly acceptable rating from the respondents.